Sequence-based diversity of 23 autosomal STR loci in Koreans investigated using an in-house massively parallel sequencing panel. (September 2017) - Kim, Eun Hye; Lee, Hwan Young; Kwon, So Yeun; Lee, Eun Young; Yang, Woo Ick; Shin, Kyoung-Jin
Highlights: Twenty three autosomal STRs were investigated in 250 Koreans using an in-house MPS panel. MPS results of 23 autosomal STRs were 99.97% concordant with those of CE results. D12S391 and D21S11 exhibited, respectively, the highest number of alleles and genotypes by the MPS analysis. SNPs and/or Indels were observed in the flanking region of D1S1656, D2S441, D5S818, D7S820, D13S317, D16S539, D21S11, and Penta D. The developed MPS panel can be successfully applied to forensic DNA databasing and casework analysis. Abstract: As DNA databases continue to grow and international cooperation increases, forensic STR loci have expanded to increase the discriminatory power and inter-database compatibility. Current capillary electrophoresis (CE) and/or massively parallel sequencing (MPS)-based commercial STR analysis systems reflect such changing trends of expanding STR loci. Due to the general gains of larger multiplexing and the detection of sequence variation, the application of MPS technology to STR analysis has further improved discrimination and is expected to aid in mixture interpretation by increasing the effective number of alleles. However, high-throughput analysis has rarely been reported for forensic DNA databasing. In this study, we present the sequencing results from 250 Korean samples at 23 commonly used STR loci (D1S1656, TPOX, D2S441, D2S1338, D3S1358, FGA, CSF1PO, D5S818, D6S1043, D7S820, D8S1179, D10S1248, TH01, vWA, D12S391, D13S317, Penta E, D16S539, D18S51, D19S433, D21S11, Penta D, and D22S1045) using an in-house assay designed for MPS. All amplicons in the multiplex exhibited a size range of 77 to 217 base pairs, and the barcoded library for the MPS run was easily prepared using a PCR-based library preparation method followed by sequencing on a MiSeq System (Illumina). We compared the STR genotyping results with those obtained using CE and scrutinized the sequence variations in both the targeted STR and flanking regions. MPS results of 23 autosomal STRs were 99.97% concordant with those of CE results. D12S391 and D21S11 exhibited, respectively, the highest number of alleles and genotypes by the MPS analysis. Single nucleotide polymorphisms and insertion and deletions (Indels) were observed in the flanking regions of D1S1656, D2S441, D5S818, D7S820, D13S317, D16S539, D21S11, and Penta D. Consequently, an MPS analysis of an expanded set of STRs, as demonstrated in the population statistics of a Korean population, will be of great practical use in forensic genetics.